Thromboelastography for the evaluation of coagulation function in patients with hepatic echinococcosis during the perioperative period: a retrospective study - Xing Zheng; Li Yuan; Bingxian Wang; Genkui Li; Jing Wang; Jide A; Zongzhao He (Frontiers in Oncology)
ObjectiveTo study the application of thrombolysis diagram (TEG) and routine coagulation test in the evaluation of coagulation function in patients with hepatic hydatid.MethodsThe observation group consisted of 69 cases of hydatid liver patients undergoing elective combined segmenectomy, and the control group consisted of 69 healthy subjects. The correlation analysis of TEG, six coagulation items and PLT in the preoperative observation group and control group was conducted. The differences of TEG, hemagglutination six and PLT between the two groups were compared. TEG and coagulation function indexes of observation group were compared at different time during perioperative period.ResultsIn the control group, The time of blood cell aggregation (K) was negatively correlated with prothrombin time (PT), fibrinogen (FIB) and platelet count(PLT); The maximum strength of blood clot (MA) was positively correlated with PT, FIB and PLT; The rate of blood cell aggregation (Angle) is positively correlated with PT, FIB and PLT; the comprehensive index of blood coagulation (CI) was positively correlated with FIB and PLT. The reaction time of blood coagulation (R) of observation group was positively correlated with PT; MA was positively correlated with PT, FIB and PLT; MA was negatively correlated with thrombin time (TT). activated partial thromboplastin time (APTT), D-dimer (DD), PLT, R value, K value, Angle, MA and CI were compared between the two groups, and the differences were statistically significant (P<0.05). Compared with T1, APTT, R value, Angle and MA in observation group were significantly decreased at T2 and T3 (P<0.05); Compared with T1, PT, TT, FIB and K values had no significant changes (P>0.05).ConclusionThe coagulation function of liver hydatid patients was relatively low during the perioperative period, TEG is more sensitive to changes in perioperative coagulation function and can comprehensively understand the patient’s coagulation state.